Study on the effect of temperature on the reinforcement of tailings sand by microbial mineralization - Zhenhua Yang; Xuezeng Wang; Xiaoshuai Liu; Longkang Liu; Yanrong Dong (Case Studies in Construction Materials, 2024)
Currently, more attention is focused on the durability of microbial mineralization solidification of sandy soil in high-temperature environments to enhance the unconfined compressive strength (UCS), while with less emphasis on the immobilization effect on heavy metals. Lead (Pb)-zinc(Zn) mining tailings (LZMT) has the characteristics of loose soil and the release of heavy metal pollutants. This experiment, based on the microbial mineralization curing technology, using LZMT as raw materials to conduct microbial mineralization solidification experiments, and the effect of temperature on the microbial mineralization curing of LZMT was evaluated by using the UCS and the fixation rate of heavy metal ions as the key indexes. Combined with fourier transform infrared spectroscopy (FTIR), X-ray diffractometer (XRD), scanning electron microscope-energy dispersive spectroscopy (SEM-EDS), we revealed the mechanism of temperature affecting microbial mineralization solidification of LZMT. The results showed that during microbial mineralization solidification of LZMT, Sporosarcina pasteurii mainly removed heavy metal ions through electrostatic attraction and precipitation reactions. Temperature had almost no impact on heavy metal ions fixation rate in microbial mineralization solidification LZMT. The impact of temperature on UCS of microbial mineralization solidifying LZMT specimens showed an initial increase then decrease trend. The UCS was maximum at 125°C, reaching 1.53 MPa, which was 47 % higher than the UCS at 50°C. This study is instructive for the application of LZMT in the field of building materials.